Efficacy and Safety of Autologous Stem-Cell Transplantation as Part of First-Line Treatment for Newly Diagnosed Primary Central Nervous System Lymphoma: A Systematic Review and Meta-Analysis - Liu, Jing; Guo, Jiayuan; Sun, Xuefei; Liu, Yuanbo; Gao, Chunji (Frontiers in Oncology, 2022)
Objective: The reviewed literature supports a treatment regimen for primary central nervous system lymphoma (PCNSL) that includes induction chemotherapy followed by one consolidation therapy. High-dose chemotherapy supported by autologous stem-cell transplantation (ASCT) is the most studied option, but its effects are controversial. The aim of this study was to evaluate the efficacy and safety of ASCT for newly diagnosed PCNSL by means of a meta-analysis. Methods: The PubMed, Embase, and Cochrane Library databases were systematically searched for studies published through 20 May 2021. Included studies were prospective studies of patients with newly diagnosed PCNSL treated with ASCT. The pooled rates and 95% confidence intervals (CIs) for all outcomes. Subgroup analysis was conducted to compare the relative risk (RR) with 95% CIs for the complete remission (CR) rate, and the hazard ratios (HRs) with 95% CIs for progression-free survival (PFS) and overall survival (OS). Results: Thirteen prospective studies including 348 patients were analyzed. The pooled CR rate, overall response rate and relapse rate were 80% (95% CI, 71–88%, I2 = 67.06%, p = 0.00), 95% (95% CI, 87–100%, I2 = 73.65%, p= 0.00) and 19% (95% CI, 15–24%, I2 = 76.18%, p = 0.00), respectively. The pooled 2-, 5-year PFS and OS rates were 74% (95% CI, 68–80%, I2 = 3.90%), 65% (95% CI, 51–77%, I2 = 74.61%), and 80% (95% CI, 72–88%, I2 = 57.54%), 69% (95% CI, 53–83%, I2 = 83.89%), respectively. Haematological toxicity and infections were more common adverse events above grade 3. The pooled treatment-related mortality was 3% (95% CI, 1–6%, I2 = 28.18%, p = 0.16). Group analysis of ASCT compared with whole-brain radiotherapy, there were no significant differences in the CR rate (RR, 1.00, 95% CI, 0.88–1.14, p = 0.971), relapse rate (RR, 0.44, 95% CI, 0.06–3.10, p = 0.408), PFS (HR, 1.28, 95% CI, 0.81–2.01, p = 0.29) or OS (HR, 1.62, 95% CI, 0.97–2.69, p = 0.06). Cognitive functions were preserved or improved after ASCT. Conclusions: ASCT is a feasible approach for consolidation with good tolerability for newly diagnosed PCNSL patients. High-quality randomized-controlled trials are still needed to confirm the effects of ASCT.